Optimized Placement of Voltage Sag Monitors Considering Distributed Generation Dominated Grids and Customer Demands - Wang, Ying; He, Haishan; Fu, Qiang; Xiao, XianYong; Chen, Yunzhu (Frontiers in Energy Research, 2021)
Voltage sag causes serious economic losses to sensitive customers. However, the existing optimal placement methods of sag monitors ignore the economic needs of customers. The optimal placement model of voltage sag monitor is proposed in this paper, which considers the sag economic loss weight, realizes the redundant coverage of important customers, and reduces the risk of sag loss of them. The model is also suitable for the system with a large number of DG access. Firstly, the calculation model of exposed area based on Chebyshev iterative method is established to obtain the system exposed area quickly, and the influence of DG replacing traditional generator on exposed area and economic loss is analyzed qualitatively. Then, the economic loss is quantitatively evaluated based on the exposed area. What’s more, the priority of important customers is determined accordingly, and the optimal placement model of sag monitor is proposed. Finally, simulation results show that in large-scale DG access, the customer’s economic loss caused by sag will increase. Compared with traditional methods, this method can reduce the risk of loss and ensure the economic benefits of important customers.